Enzymatic synthesis of ester prodrugs of acyclic nucleoside analogues by Candida antarctica lipase - Lamatová, N. (Nikola); Krečmerová, M. (Marcela); Spiwok, V.; Brabcová, J. (Jana) (2015)
New enzymatic method of transesterification of DHPA, acyclovir and ganciclovir using various vinyl esters differing in lenghts of aliphatic chains catalyzed by immobilized Candida antarctica lipase was worked out.